An Efficient Method in Real Time for Water Quality Monitoring Using Internet of Things - Bhagavan, K; Vamsi Krishna, R; Chandu Lakshmi Gangadhar, A; Arun, M (International Journal of Engineering and Technology, 2018)
In this day and age, Internet of Things (IoT) and Remote Sensing (RS) procedures are being utilized as a part of various regions of research for observing, gathering and breaking down information from remote areas. Drinking water is a valuable product for every single individual as drinking water utilities confront a considerable measure of new difficulties progressively activity. These difficulties start in light of restricted water assets, developing populace, maturing foundation and so on in this way there is a requirement for better techniques to screen the water quality. Keeping in mind the end goal to guarantee the protected and providing of drinking water the quality ought to be checked progressively. In this paper we intend to present the arrangement and development of a minimal attempt framework for genuine observing of water quality in an IoT situation. The structure comprises of a few sensors which are utilized for estimating physical and substance parameters of water [1]. The frameworks, for example, temperature, pH, turbidity, conductivity, broke down oxygen of the water can be estimated. Utilizing this framework a man can recognize toxins from a water body from anyplace in the world.Â
Keywords: Iot; Cloud; Microcontroller; Sensors; Water parameters.